Kesejahteraan Psikologi dengan Stres Kerja Karyawan Pada Masa Pandemi Copid-19 - Mellsy Todaga; Sutarto Wijono (Kuras Institute, 2022)
This study aims to determine the relationship between psychological well being and work stress on employees of PT work form home during the pandemic. Participants in this study were employees who worked at PT with a total population of 37 participants. The research method used in this study is a quantitative approach, with a non-probabilty sampling technique, namely saturated sampling by taking the entire population of 37 participants. Measurement of psychological well being using the instrument used in this study came from Ryff's character whose research scale has been modified and adapted to the context to be studied. Ryff to measure psychological well being with Cronbach alpha 0.624 while to measure work stress using the work stress scale according to Robbins (2013) and cronbach's alpha of 0.825. The scale is distributed in the form of a questionnaire, with data analysis using IBM SPSS Statistics version 21 and correlation test using product moment from Karl Pearson. The results of data analysis obtained correlation coefficient r r = 0.235; p>0.05. This means that the results of the study do not have a significant relationship. Thus, the research hypothesis which reads that there is a negative relationship between psychological well being and work stress, psychological well being and work stress of employees working from home during the pandemic at PT is rejected.